Quantitative metaproteomics of medieval dental calculus reveals individual oral health status. Issue 1 (December 2018) - Jersie-Christensen, Rosa; Lanigan, Liam; Lyon, David; Mackie, Meaghan; Belstrøm, Daniel; Kelstrup, Christian; Fotakis, Anna; Willerslev, Eske; Lynnerup, Niels; Jensen, Lars; Cappellini, Enrico; Olsen, Jesper
Abstract The composition of ancient oral microbiomes has recently become accessible owing to advanced biomolecular methods such as metagenomics and metaproteomics, but the utility of metaproteomics for such analyses is less explored. Here, we use quantitative metaproteomics to characterize the dental calculus associated with the remains of 21 humans retrieved during the archeological excavation of the medieval (ca. 1100–1450 CE) cemetery of Tjærby, Denmark. We identify 3671 protein groups, covering 220 bacterial species and 81 genera across all medieval samples. The metaproteome profiles of bacterial and human proteins suggest two distinct groups of archeological remains corresponding to health-predisposed and oral disease-susceptible individuals, which is supported by comparison to the calculus metaproteomes of healthy living individuals. Notably, the groupings identified by metaproteomics are not apparent from the bioarchaeological analysis, illustrating that quantitative metaproteomics has the potential to provide additional levels of molecular information about the oral health status of individuals from archeological contexts. Mineralized plaque, or dental calculus, is a valuable reservoir of the ancient oral microbiome. Here, the authors use quantitative metaproteomics to analyze the dental calculus of 21 individuals from a medieval cemetery, identifying human and microbial proteins that shed light on their oral health status.